THE ROLE OF MATHEMATICS REALISTIC EDUCATION APPROACH ON STUDENTS’ MATHEMATICAL CRITICAL THINKING AND RESILIENCY - Murni, Sukma; Sugandi, Asep Ikin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The purpose of this study is to analyze  the role of mathematics realistic education (RME)  approach on students’ mathematical critical  thinking  and resiliency. This study is an experiment with pre test-post test control group design and involves 62  eleventh grade students, a mathematical critical  thinking test, a mathematical  resiliency scale, and a perception on RME approach scale. The study found, on mathematical critical   thinking  ability (MCTA), its N Gain, and  mathematical resiliency (MR) students getting treatment with RME approach attained better grades than the grades  of students taught by conventional teaching. The first group students attained at medium grade level on MCTA and fairly good grade level on MR, while the second group students  obtained  at low grade level on MCTA, medium grade level on MR, and they realized difficulties in some  items of  mathematical critical  thinking tasks. The other findings, there was no association between MCTA and MR, and students learned actively, thought critically and creatively, were unafraid to pose their opinion and performed to be  self confident during  RME approach.